Research with children: methodological and ethical issues - Carvalho, Graça Simões de (2018)
Research with children is a matter of intense discussion nowadays. Some researchers perceive research with children as being just the same as with adults, others as entirely different, and other researchers are between these two poles. The way researchers perceive children and childhood (such as children being social competent actors) has implications for the research process with children and affect the ways of listing to them. In this talk, general areas of differences between research with adults and children will be discussed, giving particular emphasis to issues of ethics and imposing researcher’s perceptions (critical reflection of the use of ‘child centered’ methods), validity/reliability (children may exaggerate or lie to please the researcher), language clarity (language appropriate to children’s age), research context (setting where children are at easy), building rapport (empathy making to create a trusting zone of rapport), data analysis (care to interpret children’s perspectives), appropriate research methods (using children’s preferred methods and familiar sources). Research task-based methods make research fun for children and tap into their interests. The following task-based methods will be presented and discussed: drawings, photographs, spider diagrams, diaries, interviews and questionnaires. In short, even considering that children are socially competent actors, researchers must be critically aware of the reasons why research with children may be, in some aspects, different from adults.